Amish of Marigold : The Marriage Pact - Book 3 - Fuller, Kathleen (Thorndike, Maine : Center Point Large Print, 2025)
"Perry and Daisys fake relationship is fooling everyone . . . but theyre the ones who might be getting fooled. When Daisy Hershberger and Perry Bontrager meet, they discover they have one thing in common: both their families are way too eager to see them make a good match. Daisy is convinced that Maynard is the one for her, but her parents have their doubts. And Perry? His family wonders if theres anyone out there for a quirky guy like him. Hes also certain that some people -- himself included -- are destined to be single for life. After comparing notes, Perry and Daisy agree to a pact. Hell help her make Maynard realize what hes missing, and shell pretend to be Perrys love interest to keep his matchmaking mother satisfied. For a while, their pact seems to be working. Maybe their imagined futures arent exactly what fairy tales are made of, but theyre committed to their plan . . . until they realize that a real-life fairy tale is happening where they least expect it. Sometimes, you dont have to pretend to be anything but yourself in order for love to find you."--
Keywords: Amish -- Ohio; Fiction; Man-woman relationships -- Fiction; Families -- Fiction; Deception -- Fiction; Ohio -- Fiction; Christian fiction; Romance fiction; Large print books